Industrial training report: Perpustakaan Tun Abdul Razak, UiTM Cawangan Selangor Kampus Puncak Alam / `Arif Zulhakim Zulkiflie - Zulkiflie, `Arif Zulhakim (Faculty of Information Management, 2022)
The introduction, organization of information, industrial training activities, and conclusion are the four chapters of this industrial training report. The background of the organization is covered in Chapter 1, and the structure and function of the departments are covered in Chapter 2. Chapters 3 and 4 contain training exercises and special projects, respectively, while chapter 4 contains the report’s conclusion. Trainees must complete 5 months of practical training in industry between March 1 and July 21,2022, in order to finish their studies. “PTAR UiTM Puncak Alam Campus” is the library that the trainee has chosen. Main Library, PTAR Puncak Alam Campus, PTAR Puncak Perdana Campus, PTAR Complex of Architecture, PTAR Sungai Buloh, Selayang & Teluk Intan Campus, PTAR Dengkil Campus, and PTAR UiTM Hospital are the five branch libraries on UCS (UiTM Cawangan Selangor).